Hubungan antara Dukungan Keluarga dengan Perilaku Ibu dalam Pemberian ASI Eksklusif DI Desa Trenyang Wilayah Kerja Puskesmas Sumberpucung - Ririn Kurniawati; Wyssie Ika Sari; Dita Islamiah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Mother's Milk (ASI) is the best food that contains all nutrients needed by infants aged 0-6 months. Breast milk can affect the growth and development of bayp. The purpose of this study was to identify the relationship between family support and mother's behavior in providing exclusive ASI in the trenyang village Sumber Pucung health center. This research was conducted with a case control approach. The variable in this study is the dependent variable family support, the independent variable exclusive breast feeding. The research was carried out in trenyang village, the working area of Sumber Pucung, sampling purposive sampling with a large sample of 96 infants aged 7-24 months. Date were then tested using chi square analysis. Chi squere test results obtained p (0.015) <0.05 then H1 is accepted and rejected by H0, which means there is a relationship between family support and maternal behavior in providing exclusive breastfeeding in trenyang village Sumber Pucung. And the value obtained OR = 2.77 means that family support gives 2.77 times the opportunity for family support. Conclusion of this research is all family give support to mother's behavior in providing exclusive ASI health officer should increase cooperation with mom family because support will increase the mom’s self supporting. Health workers are expected to increase cooperation with Posyandu cadres because family support will increase independence for mothers in exclusivebreastfeeding.